Tuberculous epididymo-orchitis masquerading as acute scrotum - Kinnear, Ned (BMJ Case Rep, 2016)
An 18-year-old boy, a refugee from Afghanistan, with no significant medical history, presented after 1 day of severe left testicular pain. History, clinical examination and scrotal ultrasound suggested the diagnosis of epididymo-orchitis. He was discharged on a 2-week course of amoxicillin/clavulanic acid. Six weeks later, he re-presented with a testicular abscess, continuous with the epididymal head. Incision and drainage led to laboratory confirmation of tuberculous infection. He was treated with isoniazid, rifampicin, ethambutol, pyrazinamide and vitamin B(6) for 9 months, with good response. Despite meeting high-risk criteria for tuberculosis, our patient had a delayed diagnosis. We present the case and discuss the lessons learned.